Review of the process of IT operations for a health services company - Flores Masías, Edward José (2019)
The objective of this research is to perform the evaluation of the General IT Controls in Operations Management implemented by the systems management of a health services company, to determine if the established controls can reduce the potential risks to acceptable levels , based on good practices that exist in the framework of COBIT 5 work and aimed at measuring the degree of confidence of controls in systems that affect financial statements within a company. In the detailed description of the review structure, the corresponding processes were evaluated and opportunities for improvement were identified. Finally, based on the analysis performed and the results obtained, necessary recommendations will be provided, so that the company can solve the problems encountered in order to improve profitability, in the audit carried out on information security and the efficiency of the systems analyzed.